Tom Bingham and the transformation of the law : a liber amicorum - d; Fairgrieve, Duncan; Markesinis, B. S.; McKendrick, Ewan.; Rix, Bernard Anthony, Sir, 1944- (Oxford : Oxford University Press, 2009)
Tom Bingham is among the most influential judges of the 20th century. This volume collects around 50 essays from colleagues and those influenced by Lord Bingham, from across academia and legal practice. The essays survey Lord Bingham's pivotal role in the transformations that have taken place in the legal system during his career.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Bingham, T. H. -- 1933-2010.; Judges -- England -- Biography; Law -- England; International and municipal law -- Great Britain